TCSC: A Solution to Controllable Series Compensation (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
Controllable series compensation is a useful technique to increase the efficiency of operation of existing transmission lines and improve overall power system stability. Up to date, the TCSC is the most adopted solution whenever controllable series compensation is required. This paper introduces the Thyristor Controlled Series Capacitor (TCSC), a novel FACTS device for series compensation.The principle of operation and some prospective applications of the equipment are presented. Series Capacitive Compensation was introduced decades ago to cancel a portion of the reactive line impedances & thereby increase the transmittable power.Controllable Series Line Compensation is a cornerstone of FACTS technology. It can be applied to achieve full utilization of transmission assets.
Keywords: Series Compensation; TCSC; GCSC; FACTS